KONSTRUKSI REALITAS PEMBERITAAN WACANA SYIAH PADA MEDIA ONLINE ORMAS SYIAH INDONESIA - Ahmad Fahrur Rozi; Ade Solihat (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
Abstract This research aims to analyze the construction of Shia discourse published in the official online media of Indonesian Shia mass organizations and how Shia media can survive amidst the siege of Sunni mainstream media in Indonesia. This research stems from the background of Shiites as a minority in Indonesia and the massive anti-Shia propaganda campaign created by sunni conservative groups. This is a qualitative research using content analysis methodology. This article used Ibn Hamad's media and reality construction theory and Erving Goffman's stigma theory. Using these theories the author found; first, referring to media and reality construction theory, it was found that the construction of Shia discourse in Indonesian Shia online media tends to display the language symbols of "peace", “pluralism”, “religious moderation”, "brotherhood" and "nationalism". This discourse has implications for the image of Indonesian Shiites who are not heretical and appear to be actively voicing a religious moderation attitude. Second, referring to stigma theory, Shia online media is adaptive to mainstream Sunni media issues to gain formal or moral recognition in front of the majority of Indonesian Sunni Muslims. Furthermore, this article will open further research related to the survival of minorities as well as related to the cyber media issue for religious mass organizations in Indonesia. Keywords: Shia, Sunni, Online Media, Discourse, Construction Abstrak Penelitian bertujuan untuk menganalisis konstruksi pemberitaan wacana syiah yang dimuat dalam media-media online resmi ormas syiah Indonesia serta bagaimana media syiah dapat survive di tengah kepungan media mainstream sunni di Indonesia. Penelitian ini Berangkat dari latar belakang syiah sebagai kaum minoritas di Indonesia dan masifnya gerakan propaganda kampanye anti syiah di media-media online. Penelitian ini merupakan penelitian kualitatif yakni berupa konten analisis. Adapun teori yang digunakan dalam penelitian ini ialah teori media dan konstruksi realitas Ibnu Hamad dan teori stigma Erving Goffman. Melalui teori tersebut penulis menemukan beberapa temuan. Pertama, mengacu pada teori media dan konstruksi realitas, ditemukan bahwa kontruksi wacana syiah dalam media online syiah Indonesia cenderung menampilkan simbol-simbol bahasa “perdamaian”, “pluralism”, “moderasi agama”, “persaudaraan”, dan “nasionalisme”. Wacana tersebut berimplikasi terhadap citra syiah Indonesia yang tidak sesat dan nampak aktif menyuarakan sikap moderasi agama. Kedua, mengacu kepada teori stigma, media online syiah adaptif terhadap isu-isu mainstream media sunni dengan tujuan mendapatkan pengakuan secara formal ataupun moral di hadapan mayoritas muslim sunni Indonesia. Lebih lanjut artikel ini akan membuka penelitian lebih jauh terkait survival kaum minoritas serta terkait isu media ciber ormas kegamaan di Indonesia. Kata kunci: Syiah, Sunni, Media Online, Wacana, Konstruksi